The complete mitochondrial genome sequence of Microphysogobio tafangensis (Cypriniformes: Cyprinidae). (2nd January 2016) - Wang, Heng; Yang, Xiaoxue; Wang, Xiarong; Cai, Lingchao; Yang, Shoubao; Wei, Min; He, Liping; Li, Chen
Abstract: In the present study, the total mitochondrial genome of Microphysogobio tafangensis (Cypriniformes: Cyprinidae) was determined. The full genome was 16, 683 bp in length, which consisted of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and 2 non-coding regions. The nucleotide composition of M. tafangensis mitochondrial genome was A: 29.38%, G: 17.71%, T: 25. 47% and C: 27.44%.